'Bringing everyone on the same journey': revisiting inclusion in higher education. Issue 8 (3rd August 2019) - Collins, Ayse; Azmat, Fara; Rentschler, Ruth
ABSTRACT: This study investigates inclusion in higher education, examining learning environments for students with physical disabilities (SWPD) and the challenges faced in promoting inclusive education, using an Australian university as a case study. Drawing from the social model of disability and interviews with 40 stakeholders, our findings suggest that despite marked progress towards inclusive education through reasonable adjustments for all, learning environments remain largely driven by adjustments for individual students, creating organisational and personal challenges. Four key challenges emerged: (1) staff perception about too many resources creating student dependencies; (2) staff training needs; (3) low representation of students with visible disabilities; and (4) moving inclusion beyond education into employment. Our findings emphasise the need to embed employability and skills development in all aspects of teaching and learning while moving towards inclusive education, to enable all students to develop professionally, and reinforcing calls for an inclusive workplace that values and accepts SWPD.